2017
DOI: 10.1002/2017jc013099
|View full text |Cite
|
Sign up to set email alerts
|

Remote‐Sensing Estimation of Phytoplankton Size Classes FromGOCISatellite Measurements in Bohai Sea and Yellow Sea

Abstract: Phytoplankton size class (PSC), a measure of different phytoplankton functional and structural groups, is a key parameter to the understanding of many marine ecological and biogeochemical processes. In turbid waters where optical properties may be influenced by terrigenous discharge and nonphytoplankton water constituents, remote estimation of PSC is still a challenging task. Here based on measurements of phytoplankton diagnostic pigments, total chlorophyll a, and spectral reflectance in turbid waters of Bohai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 91 publications
3
19
0
Order By: Relevance
“…The spatial and temporal distribution of satellite-derived chlorophyll-a concentration and PSCs in this study are in agreement with previous in situ observations and remote sensing estimations (Fu et al, 2010(Fu et al, , 2009Huang et al, 2010;Sun et al, 2017Sun et al, , 2019Sun et al, , 2002Sun et al, , 2012Sun et al, , 2018. High chlorophyll-a concentration and large cell phytoplankton biomass were observed in entire BS and nearshore YS (Figures 6 and 7).…”
Section: Spatial and Temporal Variations Of Chlorophyll-a Concentratisupporting
confidence: 92%
See 1 more Smart Citation
“…The spatial and temporal distribution of satellite-derived chlorophyll-a concentration and PSCs in this study are in agreement with previous in situ observations and remote sensing estimations (Fu et al, 2010(Fu et al, , 2009Huang et al, 2010;Sun et al, 2017Sun et al, , 2019Sun et al, , 2002Sun et al, , 2012Sun et al, , 2018. High chlorophyll-a concentration and large cell phytoplankton biomass were observed in entire BS and nearshore YS (Figures 6 and 7).…”
Section: Spatial and Temporal Variations Of Chlorophyll-a Concentratisupporting
confidence: 92%
“…Each approach has its own advantages and limitations (Mouw et al, ). Many of these approaches have been designed for global ocean applications (Brewin et al, ; Bricaud et al, ), and some regional studies have also been conducted (Brotas et al, ; Lamont et al, ; Sun et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…GOCI-derived PSCs' distribution showed that microplankton and nanoplankton were generally the major contributors to coastal and transitional regions, and picoplankton was found to be abundant in the oligotrophic regions ( Figure 5), which was consistent with in situ investigations in our study (Figure 2), previous studies in the BS, the YS, and ECS (e.g., Fu et al, 2009;Huang et al, 2006;Sun et al, 2002Sun et al, , 2012, and from other study areas (e.g., Arin et al, 2002;Chisholm et al, 1988;Madariaga & Orive, 1989;Marañ on et al, 2001). Similar distribution of GOCI-derived PSCs was observed from our study ( Figure 5) and the study of Sun et al (2017). However, slight differences existed in the nearshore BS and SYS where microplankton instead of nano and picoplankton was dominant in our study, which might result from regional data sets for modeling and time scales utilized in the two studies.…”
Section: Spatial Distribution Of Pscssupporting
confidence: 92%
“…The geostationary ocean color imager (GOCI), the world's first geostationary ocean color satellite sensor, observes the Northeast Asian region eight times within a day from 08:15 am to 3:15 p.m. local time (temporal resolution of 1 h). In the visible region, GOCI contains six visible wavebands with central wavelengths of 412, 443, 490, 555, 660, and 680 nm and two NIR wavebands with central wavelengths of 745 and 865 nm, and has a spatial resolution of 500 m [18,36]. The GOCI satellite observations with fine temporal and spatial resolutions facilitate more detailed analysis (e.g., diurnal dynamics) for monitoring Z sd in our study area.…”
Section: Satellite Datamentioning
confidence: 99%
“…Compared to polar-orbiting satellite sensor, the geostationary satellite sensors can provide observations at a short revisit period to monitor the daily dynamics of water clarity. As the world's first ocean color geostationary satellite sensor, the geostationary ocean color imager (GOCI) provides near real-time observations over northeast Asia (including Lake Taihu as our study region), with hourly intervals up to eight times a day and the spatial resolution of 500 m [18]. Thus, the GOCI satellite data are very useful to monitor the water transparency in submesoscale regions such as the estuaries and large individual lakes.…”
Section: Introductionmentioning
confidence: 99%